Simulation of subsea seismic ground motions - Hao, Hong; Bi, Kaiming; Li, C.; Li, H. (2017)
© 2017 Taylor & Francis Group, London. Seismic motions at seafloor are different from those at onshore sites since seawater can significantly suppress the seafloor vertical motions at the P-wave resonant frequencies of the seawater layer. Seawater layer also indirectly influences the seafloor motions as it changes the water saturation level and pore pressure of subsea soil layers. This paper summarizes some recent developments on the study of characteristics of subsea ground motions, and simulations of seismic motions at seafloor for use in seismic response analysis of offshore structures. The theoretical seafloor transfer functions are presented first. Procedures of simulating seafloor motions from the base rock motion spectrum or using onshore earthquake recordings are introduced. A numerical example is provided following the corresponding theoretical background in each section to demonstrate the procedure. The procedures can be used to simulate seafloor motions that can be used as inputs in the seismic response analysis of offshore structures.